THE IMPLEMENTATION OF AKAD IJARAH ON WORKER WAGE SYSTEM OF BATIK FABRIC PRODUCTION - Annajah, Dinda Safinah; Imtikhanah, Sobrotul; Hudaya, Fadli (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The study is a qualitative one, it aims to answer the problems statements; whether the forms of work, working time, wages, and labour devoted to the production of batik cloth in Batik Larissa and Batik Feno are in accordance with the Islamic view. The method applied here is to analyse data based on the fact obtained from the field. Meanwhile, interviews and documentations with the related parties; the owner and the labour of Batik Larissa and Batik Feno. The result obtained is the forms of work is in accordance with the existing work contracts in Batik Larissa and Feno. In the initial agreement on terms of working time, it was stated that only the contracted time was set without targeting the amount of work to be done. For the wages, the process in Batik Larissa and Feno are appropriate and equal to the enthusiasm of the workers to work. The wages have been paid daily and piece rates are given when the work has been completed. Furthermore, the workers are not forced to devote their energy excessively, only according to their ability. Based on the result stated above, it is expected for the owners in procedures of paying the workers to be always fosters mutual trust and honesty between the two parties so that it does not cause uncertainty or gharar regarding the wages and does not cause disappointment to workers. And for the wage’s procedures, it must always be adjusted to the share of participation, the type of work performed, the volume of work, and the proportion of work.